Type 2 cytokines sensitize human sensory neurons to itch-associated stimuli - Mack, Madison R.; Miron, Yannick; Chen, Fanny; Miller, Paul E.; Zhang, Annie; Korotzer, Andrew; Richman, Daniel; Bryce, Paul J. (Frontiers in Molecular Neuroscience, 2023)
Chronic itch is a central symptom of atopic dermatitis. Cutaneous afferent neurons express receptors for type 2 cytokines, including interleukins (IL)-4, IL-13, and IL-33, which are elevated in atopic dermatitis. These neuronal cytokine receptors were found to be required in several murine models of itch. Prior exposure of neurons to either IL-4 or IL-33 increased their response to subsequent chemical pruritogens in mice but has not been previously examined in humans. The objective of the present study was to determine if type 2 cytokine stimulation sensitizes sensory neurons to future itch stimuli in a fully human ex vivo system. We measured calcium flux from human dorsal root ganglia cultures from cadaveric donors in response to pruritogens following transient exposure to type 2 cytokines. We also measured their effect on neuronal calcium flux and changes in gene expression by RNA sequencing. Type 2 cytokines (IL-4, IL-13, and IL-33) were capable of sensitizing human dorsal root ganglia neurons to both histaminergic and nonhistaminergic itch stimuli. Sensitization was observed after only 2 hours of pruritogen incubation. We observed rapid neuronal calcium flux in a small subset of neurons directly in response to IL-4 and to IL-13, which was dependent on the presence of extracellular calcium. IL-4 and IL-13 induced a common signature of upregulated genes after 24 hours of exposure that was unique from IL-33 and non-type 2 inflammatory stimuli. This study provides evidence of peripheral neuron sensitization by type 2 cytokines as well as broad transcriptomic effects in human sensory ganglia. These studies identify both unique and overlapping roles of these cytokines in sensory neurons.